Implementasi Sistem Payment Toll Dengan Barcode Reader Berbasis Mikrokontroler - Yultrisna Yultrisna; Yul Antonisfia; Andi Syofian (Situs resmi ITP Press, 2019)
Nowadays, to pass through the toll road, mostly riders often complain that the queue is quite long and quite long. Implementing Tool for Toll Payment Systems Using a Microcontroller-based Bar Code Reader is designed to facilitate transaction processing and make the time spent in the process of using the toll road more efficient. This paper describes the process of making automatic vehicle detection devices so that drivers do not need to stop to process the toll road usage. This tool is designed using a barcode reader as input data, Ethernet shield as an internet network (local), Arduino Uno as a process controller in sending data from barcode reader into SPT application, servo motor / as a driver to automatically open the gate and Android as notification/notification for toll road users. From the results of testing all input and output functions can be performed. In testing using a toy car unit, the reading distance of the barcode with the barcode reader is ± 7cm. In this case, the system can run well and has a pretty good performance because the barcode reader can read a maximum of ± 15cm.